PREVALENCE AND FACTORS ASSOCIATED WITH THYROID DYSFUNCTION AMONG PREMATURE BABIES IN A SELECTED TERTIARY CENTRE IN MALAYSIA - Salam, Fatinah Abdul; Musa, Maizatul Akmar; Lee, Yee Lin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Premature babies have a higher risk of developing thyroid dysfunctions due to immaturity of hypothalamic-pituitary-thyroid (HPT) axis. Rescreening of thyroid function is recommended in Malaysia among preterm babies ≤34 weeks gestation since 2022 to improve detection of thyroid dysfunction with delayed TSH rise. This study aims to analyse the prevalence and factors associated with thyroid dysfunction in preterm babies ≤34 weeks gestation and to evaluate its progression and outcome. METHODOLOGY A retrospective study was performed among premature babies ≤34 weeks of gestation born between January 2019 until August 2024 in a selected NICU in Malaysia. Infants who had at least one repeated thyroid function test (TFT) after birth were included in the study. Data on the demographic factors and clinical characteristics were collected from the medical records. The TFT of the study population and its progression were analysed. RESULT There were 14% (46/320) infants with thyroid dysfunction. The majority of infants with thyroid dysfunction had subclinical hypothyroidism 84.7% (39/46), followed by thyroid hypothyroxinemia of prematurity (THOP) 8.7% (4/46) and primary hypothyroidism 6.5% (3/46). Out of the 46 patients with thyroid dysfunction, 18/46 (39.1%) were detected at <2 weeks of life, 20/46 (43.5%) were detected at 2–4 weeks old and 8/46 (17.4%) were detected after 4 weeks old. In the evaluation of factors associated with thyroid dysfunction, only small for gestational age (SGA) was significantly associated with thyroid dysfunction compared to infants without SGA (28.2% vs 14.2%, p = 0.017). Only 15/46 (32.6%) of infants with thyroid dysfunction required levothyroxine replacement, all of whom had primary and subclinical hypothyroidism. All infants with THOP had spontaneous resolution of thyroid dysfunction without treatment. CONCLUSION The prevalence of thyroid dysfunction in preterm babies ≤34 weeks was 14%. The majority were detected between 2–4 weeks old. SGA was significantly associated with thyroid dysfunction in this study population.